Guns, Southernness, and gun control - Brennan, Pauline Gasdow (Journal of quantitative criminology, 1993)
Southerners have been found to have higher levels of gun ownership than persons who reside elsewhere. This may be due to cultural factors peculiar to the Southern region. If so, this would have interesting implications for gun control initiatives. Although the differential in gun ownership has been linked to varying support or opposition to gun control, the relationship between this variable and specific types of gun control has not been examined. With this in mind, we investigate how specific types of gun ownership interact with Southernness, controlling for the effects of other variables, to determine preferences for three different types of gun control. We use 1975 data collected by DMI on a stratified random sample of 1538 noninstitutionalized adults in the United States. An analysis of several logistic regression equations indicates that a cultural component, related to Southernness, affects attitudes toward gun control. Southerners, in general, were the most opposed to permits and handgun bans. Southern shotgun owners, in particular, were found to be the most opposed to gun registration. These findings point to the need to consider region, culture, and gun type when addressing the issue of gun control.